A mutation in v-src that removes a single conserved residue in the SH-2 domain of pp60v-src restricts transformation in a host-dependent manner. - Verderame, M F (1989)
The v-src oncogene of Rous sarcoma virus (RSV) is able to transform both avian and mammalian cells, but the mutant allele v-src-L displays a host range dependence for transformation, transforming chicken but not rat cells with wild-type efficiency. This host range restriction can be detected by measuring growth in low serum, saturation density, and anchorage independent growth. In addition, rat cells expressing v-src-L do not form tumors in syngeneic rats or nude mice, but RSV carrying the mutant allele causes tumors in chicks, although at a reduced efficiency and with increased latency. To determine the lesion responsible for this phenotype, we sequenced the entire v-src gene from the parental B77 strain of RSV, as well as the mutant allele. v-src-L is missing 3 nucleotides present in the wild-type parent, RSV B31, eliminating Phe-172, an invariant residue in a conserved region of src-related proteins known as SH-2. The kinase activity of pp60v-src-L was indistinguishable from that of the wild type in chicken cells but was significantly reduced in rat cells as assayed by an in vitro immune complex assay; in vivo phosphorylation of one specific substrate, p36 (calpactin I heavy chain); and total phosphotyrosine-containing proteins. In addition, the pattern of phosphotyrosine-containing proteins in rat cells was qualitatively different when cells containing pp60v-src-L were compared with cells with wild-type pp60v-src, even though both pp60v-src proteins were membrane associated. The data are consistent with a role for the SH-2 region in substrate specificity.